The Supreme Court of Canada : history of the institution - Snell, James G. (Heritage., 1985)
This history traces the development of the Supreme Court of Canada from its establishment in the earliest days following Confederation, through its attainment of independence from the Judicial Committee of the Privy Council in 1949, to the adoption of the Constitution Act, 1982.